2022
DOI: 10.1523/eneuro.0068-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Repeated Social Defeat Stress on Brain Activity during Social Interaction in BALB/c Mice

Abstract: Understanding the long-term effects of stress on brain function is crucial for understanding the mechanisms of depression. The BALB/c mouse strain has high susceptibility to stress and is thus an effective model for depression. The long-term effects of repeated social defeat stress (SDS) on BALB/c mice, however, are not clear. Here, we investigated the effects of repeated SDS in male BALB/c mice over the subsequent two weeks. Some defeated mice immediately exhibited social avoidance, whereas anxiety-like behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Across preclinical models of depression, markers of neuronal and metabolic activity were consistently upregulated in the habenula (n=16). The neuronal activation marker, c-Fos, was increased in the LHb following exposure to acute restraint stress (63), chronic restraint stress (47, 48), chronic inescapable shock stress (32), chronic unpredictable stress (41, 46) and social defeat stress (53, 56, 57). Only two of these studies examined c-Fos expression in male and female rodents; both studies observed sex differences in the Hb (48, 63).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across preclinical models of depression, markers of neuronal and metabolic activity were consistently upregulated in the habenula (n=16). The neuronal activation marker, c-Fos, was increased in the LHb following exposure to acute restraint stress (63), chronic restraint stress (47, 48), chronic inescapable shock stress (32), chronic unpredictable stress (41, 46) and social defeat stress (53, 56, 57). Only two of these studies examined c-Fos expression in male and female rodents; both studies observed sex differences in the Hb (48, 63).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4 studies reported that Hb neuronal activity did not significantly differ between control and depressive-like rodents; however, each of these studies supported a general trend towards greater Hb activity within the stressed cohort (39,57,64,65). One study found that c-Fos cell-count was unchanged in the MHb and LHb of rats exposed to chronic restraint stress (39).…”
Section: Markers Of Habenula Neuronal and Metabolic Activitymentioning
confidence: 99%
“…Several studies revealed a long-term increase in anxiety following chronic stress, resulting in animals spending less time in the open zones in the elevated plus maze (EPM) or increased latency to enter the zones. For social stressors, this anxiety-related behavior has been reported between one week up to a month after CSDS (Avgustinovich et al 2005;Venzala et al 2013;Warren et al 2013;Okamura et al 2022) and one week after CSC or SD/OC (Slattery et al 2012). For the non-social CUMS model, this was found up to one month after exposure (Erburu et al 2015).…”
Section: Anxiety-like Behaviormentioning
confidence: 97%
“…Nonetheless, our definition for mice should fall within the diagnostic time criterion for depression in humans, in which symptoms must persist for at least two weeks (American Psychiatric Association 2013) before they are considered a manifest clinical condition. Hence, long-term changes in mice in adult paradigms must persist for weeks and even months, which has been observed repeatedly (Avgustinovich et al 2005;Colyn et al 2019;Gellner et al 2022;Okamura et al 2022). Importantly, symptoms may occur with different latencies post stress in mice and humans, and thus both the onset and duration of stress-related effects need to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of LHb glutamatergic neurons show an opposite inhibitory response to foot shock ( 67 ). Compared with mice that exhibited social avoidance from immediately after the repeated social defeat stress, c-Fos expression in the LHb was higher in those that exhibited social avoidance only at later periods ( 68 ). This demonstrates that the activity of LHb neurons would perhaps affect different avoidance strategies to stress.…”
Section: Lateral Habenula Hyperactivity During Depressive Statementioning
confidence: 99%